An Islamic perspective on peaceful coexistence - Sulaiman, Kabuye Uthman (European Open Science Publishing, 2021)
According to Abrahamic religions, namely Judaism, Christianity and Islam, human beings exist on the earth for a common purpose,and they have patrilineally and matrilineally descended from a single couple, namely Adam and Hawa (Eve).The Qur’an unambiguously mentions:“O mankind! reverence your Guardian-Lord, who created you from a single person, created, of like nature, His mate, and from them twain scattered (like seeds) countless men and women; reverence Allah, through whom ye demand your mutual(rights), and (reverence) the wombs (That bore you): for Allah ever watches over you.”1Thus, it is incumbent upon human beings to live together in peace rather than constant hostility to fulfil the purpose of their existence on the earth. This paper endeavours to contribute to the understanding of the concept of ‘peaceful coexistence’from the Islamic perspective. It specifically answers the following research questions: What is peaceful coexistence? What is necessary for peaceful coexistence? What are the fundamental principles that we must adhere to in order to coexist peacefully? The paper is structured into eightsections, beginning with introduction on the concept of ‘peace’in Islam. The secondsection focuses on the main objectives of Islam. The third section is on the meaning of peaceful coexistence. The fourthand fifthsections are on the need for peaceful coexistence, and the necessary requirements and tools for peaceful coexistence respectively. The sixthsection is on categorization of peaceful coexistence into: peaceful coexistence in marriage, peaceful coexistence of mankind, peaceful coexistence of the members of the Muslim ummah and peaceful coexistence of mankind and the environment. The seventh section is a summary of the Islamic principles of peaceful coexistence. The final section sums up the main conclusions drawn from this study. The translation of the ayat(verses) of the Qur’an related to this study is extracted from the work of Abdullah Yusuf Ali, The Holy Qur’an: Text and Translation unless stated otherwise. At the end of this paper,it is hoped that the readers will: first, appreciate the message of Islam as a universal religion and the need for mutual care, mutual respect,and mutual cooperation; and second, explore the methodology of the Qur’an and the Prophet Muhammad (peace and blessings be upon him) in managing human diversity. It is also hoped thatthis study will lead to a better understanding of peaceful coexistence as an integral part of Islam and one of the characteristics of the Muslim ummah. The findings of this study highlight the role of Islam in promoting peace and security. The study reveals that peaceful coexistence is a key factor in the success of human beings and it requires nurturing love, respect, care, and salam (a greeting of peace) in one’s relationship with others.